Kekerasan Terhadap Perempuan Di Media Online - Reza Eka Sholehudin; Rini Sulastri (UIN Sunan Gunung Djati Bandung, 2024)
Current technological developments have made online media a source of information. More and more news about gender inequality in women appears on online media. This is caused by a lack of understanding of the meaning of gender equality, so that the lack of understanding gives rise to many gender inequalities, especially for women. The researcher's aim in researching this problem is to find out what gender inequality looks like, what factors cause gender inequality to emerge and what is behind the occurrence of cases of gender inequality in online media. The methodology used in this research is qualitative through analysis of online media data. The data taken by researchers was in the form of platforms in online media such as TikTok, Instagram and YouTube. The conclusion that can be drawn from this research is that this research aims to increase insight regarding the importance of understanding gender, especially in online media. Because gender inequality can occur at any time and by anyone.